Gambaran Pengetahuan Perawat Tentang Kelengkapan Pengisian Asuhan Keperawatan di Ruang Penyakit Dalam RSUD H. Damanhuri Barabai Tahun 2015 - Deasy Rosmala Dewi; Armiati Armiati; Anjar Retno Astrini; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
One of the factors that affect the completeness of nursing care is knowledge. Knowledge is influenced by several factors: education, experience, and age. Namely the identity of the patients 82%, 84% evaluation, planning 80%, and 80% of nurses initials. The research aim to determine the knowledge of nurses about completeness of nursing care in internist room H. Damanhuri Barabai Hospital. The method used is descriptive with the sample were 20 nurses in internist room. Knowledge of nurses towards completeness of nursing care in internist room H. Damanhuri Barabai Hospital who have a good knowledge as many as 6 respondents (30%),9 respondents (45%) have enough knowledge and 5 respondents (25%) have less knowledge.